Some new aspects of CJD epidemiology in Slovakia - Mitrová, E (European journal of epidemiology, 1991)
Descriptive epidemiological and genealogical data obtained by prospective and retrospective studies on CJD in Slovakia and in patients emigrating from CJD clusters were analysed. Observations contradictory to an exclusively genetic etiology of temporo-spatial accumulation of CJD are presented. Data indicating a genetically increased susceptibility to the disease and its coincidence with environmental risk in clustering patients are discussed.
Keywords: Female; Creutzfeldt-Jakob Syndrome; Pedigree; ženské pohlaví; Československo; rodokmen; lidé; Risk Factors; retrospektivní studie; prospektivní studie; Male; Prospective Studies; Disease Susceptibility; Creutzfeldtova-Jakobova nemoc; rizikové faktory; lidé středního věku; mužské pohlaví; Czechoslovakia; Retrospective Studies; Middle Aged; náchylnost k nemoci; Humans